Assessing parenting: Adaptation of the HOME inventory for use in Egypt - Alsharif, Khadiga Abdellatif (AUC Knowledge Fountain, 2018)
A study of violence against children in Egypt found that in 2014, 93% of children between the ages of 0-14 were subject to some form of violent discipline. While Egyptian law protects children from abuse, in practice it is challenging for social workers and other child protection practitioners to intervene. There is a lack of protocols for home visitation and family intervention, and there are no standardized procedures for assessing parenting practices and determining the safety of children’s homes. The HOME inventory, short for Home Observation for Measurement of the Environment, is a tool that has been adopted internationally and is successfully used to identify what support parents of children might need and what services could be most useful in helping them to create healthier home environments and better relationships with their children. The Infant/Toddler HOME (IT-HOME) version of the tool that addresses children aged 0-3 years was adapted for use in Egypt through translating it into Arabic and culturally adapting it to the Egyptian culture and context by child protection experts during an Expert Panel. Social workers were trained on the implementation of the tool and conducted 42 home visits to pilot test the tool, with an interrater reliability of 79% agreement. Social workers responded positively and reported that the tool helped them recognize families at risk, assess the children’s needs, and identify the necessary interventions that are appropriate for the families. The IT-HOME appears to be a promising tool that was readily accepted by both social workers and families, so with further training it could be used in Egypt as a standardized home visitation tool.